Moving through a changing world: Single cell migration in 2D vs. 3D - Pawluchin, Anna; Galic, Milos (Frontiers in Cell and Developmental Biology, 2022)
Migration of single adherent cells is frequently observed in the developing and adult organism and has been subject of intense studies. Yet, while elegant work has elucidated molecular and mechanical cues affecting motion dynamics on a flat surface, it remains less clear how cells migrate in a 3D setting. In this review, we explore the changing parameters encountered by cells navigating through a 3D microenvironment compared to cells crawling on top of a 2D surface, and how these differences alter subcellular structures required for propulsion. We further discuss how such changes at the microscale impact motion pattern at the macroscale.